الموارد البشرية ودورها في تحسين الإبداع الاستراتيجي : دراسة ميدانية - نهار، محمد عمير Nahar, Mohammed Omair (جامعة قناة السويس - كلية التجارة بالاسماعيلية, 2017)
الهدف الرئيس من هذه الدراسة هو معرفة الدور الذي تؤديه تقانة المعلومات في تعزيز مستويات الإبداع الاستراتيجي لشركات [نفط الشمال ونفط ميسان] في العراق. واستخدام الباحث المنهج الوصفي التحليلي لهذا الغرض، كذلك استخدام قائمة استقصاء كأداة رئيسية لجمع البيانات وقد بلغ حجم المجتمع [578]، كما بلغت عينة الدراسة [230] وكانت عينة عشوائية طبقية والتي ضمت المدراء ومدراء الهيئات والأقسام والشعب والوحدات والعاملين في قسم نقاتة المعلومات في كلا الشركتين، حيث تم استخدام برنامج التحليل الإحصائي [spss] كحزمة لإدخال ومعالجة وتحليل البيانات. حيث توصلت الدراسة إلى أنه لا تسعي الشركات إلى تحفيز العاملين وأشراكهم في دورات تدريبية بما يسهم في تطبيق تقانة المعلومات بالشكل الأمثل والوصول إلى الإبداع الاستراتيجي بالشركات. وكانت واهم النتائج العمل على توفير الأيادي العاملة الماهرة والقادرة على تطوير وصيانة الأجهزة وكيفية التعامل معها.
The main objective of dis study is to find out r role of information technology in promoting creativity and strategic levels of the Companies (Northern Oil and Maysan Oil) in Iraq. The researcher used the descriptive analytical method for dis purpose, as well as the Use the list of BI as a key tool for data collection has reached the size of the community (578), as was the study sample (230) and were stratified random sample, which included managers and directors of agencies and departments, divisions and units and staff in the Department of Nqath information in both the two companies, with the use of statistical analysis software (spss) as a package to input, process and analyze the data. Where the study concluded that it does not seek companies to motivate employees and involve them in training courses so as to contribute in the application of information technology as the best access to the strategic creative companies. The most important results Aalaml to provide the hands of skilled and capable of developing and maintaining the hardware and how to deal with it.
Keywords: الموارد البشرية -- الإبداع الاستراتيجي -- الاقتصاد العراقى